Non-steroidal anti-inflammatory drug use in acute myopericarditis: 12-month clinical follow-up. Issue 1 (22nd April 2019) - Berg, Jan; Lovrinovic, Marina; Baltensperger, Nora; Kissel, Christine K; Kottwitz, Jan; Manka, Robert; Patriki, Dimitri; Scherff, Frank; Schmied, Christian; Landmesser, Ulf; Lüscher, Thomas F; Heidecker, Bettina
Abstract : Objective: Clinical data on the effect of non-steroidal anti-inflammatory drugs (NSAIDs) in myopericarditis are limited. Since NSAIDs are standard therapy in pericarditis, we retrospectively investigated their safety in myopericarditis. Methods: In a retrospective case-control study, we identified 60 patients with myopericarditis from September 2010 to August 2017. Diagnosis was based on clinical criteria, elevated high-sensitivity troponin T and cardiac magnetic resonance imaging (CMR). All patients received standard heart failure therapy if indicated. Twenty-nine patients (62%) received NSAIDs (acetylsalicylic acid: n=7, average daily dose =1300 mg or ibuprofen: n=22, average daily dose =1500 mg) for an average duration of 4 weeks. To create two cohorts with similar baseline conditions, 15 patients were excluded. Three months after diagnosis, 29 patients were re-evaluated by CMR to measure late gadolinium enhancement (LGE). Results: Baseline characteristics of those treated with or without NSAIDs were similar. Mean age was 34 (±13) years, 6 (13%) were women. Mean left ventricular ejection fraction (LVEF) was 56% (±5). 82 % of the patients (14 of 17) treated with NSAIDs experienced a decrease in LGE at 3 months, while it was only 58 % (7 of 12) of those without NSAIDs (p=0.15). At 12-month follow-up, one of the patients treated without NSAIDs experienced polymorphic ventricular tachycardia (VT) with cardiac arrest, while one of the patients with NSAIDs experienced non-sustained VT. Conclusions: This is the first case-control study demonstrating that NSAIDs are safe in patients with myopericarditis and preserved LVEF. Our data suggest that this drug class should be tested prospectively in a large randomised clinical trial.